Belarus on the background of global industrial development trends. - Bajnev, Valery F.; Bliznyuсk Olga S. (Journal of the Belarusian State University. Economics, 2018)
The article is devoted to the analysis of techniques and technologies evolution in the process of civilization development. It is provided technique-technological and political-economic characteristics of the main stages of this evolution; special attention is paid to the study of the modern stage, referred to as the “fourth industrial revolution”. Its main feature istheproduction intellectualization based on the prevalence of “industrial internet” and flexible automated production systems. Trends and problems of intellectual economy formation in Belarus and other countries of the Eurasian Economic Union are analyzed, determined the ways of their solution.